(untitled) (American Journal of Energy and Natural Resources, 2023)
Micro hydro power plant remains a sustainable solution to meet the electrical needs of isolated populations when the potential is there. The discovery of new materials leads engineers to review the choice of material, in order to reduce the cost and facilitate the manufacture of hydromechanical components. In this study, to select the best choice of material for the manufacture of buckets of a micro Pelton turbine, we used multi-criteria decision support methods (MCDM) such as the Analytical Hierarchy Process (AHP), the order preference technique by similarity to the ideal solution (TOPSIS), the compromise solution (VIKOR). Based on of the literature review on the materials usable for the manufacture of hydraulic turbines, we were able to select five alternative materials such as mild steel ; aluminum alloy ; stainless steel ; high density polyethylene ; cast iron and seven very important material evaluation criteria for manufacturing such as machinability ; ultimate tensile strength ; the density ; hardness ; the cost ; maintenance cost and corrosion resistance. It appears from results via the AHP method that the coherence index of 0.0904 and the coherence ratio of 0.0669 are usable for the practice of material selection. Considering the performance scores for the five alternatives obtained via the TOPSIS and VIKOR techniques, it appears that high density polyethylene is the best material, followed by the aluminum alloy.